Application of numerical calculation methods in stability analysis of pile foundation under complex foundation conditions - Wang, Huimin; Ma, Kaiqing; Zhang, Jing; Zhang, Kai (Nonlinear engineering, 2025)
Pile foundation has been widely applied in modern civil engineering due to its excellent performance under complex foundation conditions. However, when subjected to dynamic loads such as waves, tides, and earthquakes, the long-term stability of pile foundations becomes a significant concern. Traditional stability analysis methods are predominantly based on static loading assumptions, which neglect the nonlinear behavior of soils and the time-varying characteristics of dynamic loads. This leads to reduced prediction accuracy and limited applicability under real-world, complex working conditions. To address these challenges, this study proposes an innovative numerical calculation method based on a two-parameter model, which integrates dynamic load effects – such as wave and tidal actions – into the pile-soil interaction framework. Compared with the conventional Winkler model, the two-parameter model incorporates both the stiffness of the subgrade and the shear interaction between adjacent soil springs, thereby capturing the nonlinear and spatially correlated behavior of foundation soils more accurately. The core innovations of this study lie in two aspects. First, it introduces a more refined numerical model by incorporating key parameters such as pile water entry depth, lateral soil resistance coefficient, and pile stiffness, offering a more realistic simulation of complex marine foundation conditions. Second, it performs a comprehensive stability analysis under dynamic loading environments, systematically investigating the influence of various factors including soil properties, pile length, and pile diameter on the critical frequency and overall structural stability. The research findings show that the proposed two-parameter model significantly improves the precision of stability analysis and effectively reveals the nonlinear dynamic responses of pile foundations. This contributes to both the theoretical development of pile-soil interaction modeling and practical engineering applications in marine and offshore structures.